Qualitative Research & Evaluation Methods - Patton, Michael Quinn (London Sage Publications, 2002)
The book that has been a resource and training tool for countless applied researchers, evaluators, and graduate students has been completely revised with hundreds of new examples and stories illuminating all aspects of qualitative inquiry. Patton has created the most comprehensive, systematic and up-to-date review of qualitative methods available.Patton has retained and expanded upon the Exhibits that highlight and summarize major issues and guidelines, the summative sections, tables, and figures as well as the sage advice of the Sufi Master, Halcolm. This revision will help readers integrate and make sense of the great volume of qualitative works published in the past decade. This book contains hundreds of examples and stories illuminating all aspects of qualitative inquiry. Patton has created the most comprehensive, systematic review of qualitative methods available.Key Features Explores, compares and contrasts 16 different theoretical and philosophical approaches to qualitative inquiryOffers strategies for enhancing quality and credibility of qualitative findings Unravels the complexities of mixed methods and triangulationExplains the issues and approaches to fieldwork as well as providing detailed analytical guidelines